THE EKOPUITIKA THEORY (International Journal of Education and Literature, 2022)
This study aims to: (1) describe the sense of ekopuitika theory; (2) describe the working mechanism of ekopuitika theory; and (3) describe the application of the ekopuitika theory in the oral literature. The theory used in this research is ekopuitika theory, ecology theory, and poetics theory. The data collecting technique or data collection process utilized in this research are as follows: (1) recording technique, either audio or audiovisual, (2) notes, (3) rooted interview, (4) literature study and documentation analysis. The finding of the research is (1) the meaning ekopuitika theory is literary theory/knowledge of poetry which is associated with the environment. (2) the working mechanism is started from analyzing the poetics theory which consists of: 1. Sound that includes: a) rima; (b) assonance; (c) alliteration; (d) anaphora; (e) efoni; (f) kakafoni; and (g) onomatopoeic. 2. Rime (metrum and rhythm) 3. Word includes: (a) vocabulary; (b) diction; (c) figurative language; (d) imagery; and (e) linguistic factors. 4. Phrase that includes: (a) nominal phrases; (b) verbal phrase; (c) the numeral phrase; (d) the adverb phrase; and (e) the prepositional phrase. 5. Sentence/array includes: (a) declarative sentences; (b) interrogative sentences; (c) the imperative sentence; and (d) the exclamatory sentence. 6. The discourse that includes: (a) cohesion and (b) coherence. The next how it works, is further analyzed once more with the ecology theory that includes: (a) the representation of nature: plant, animal, mountain, water, sea, land, air, sun, and sky; (b) the manifestation of the representation of behavior: traditional event (ritual), religion, knowledge, cosmology, language, myth, art, moral, and housing. After the ekopuitika theory applied in the oral literature there was a result that evidently for the representation of nature related to the plant and animal, while for the representation of the behavior associated with the traditional event (ritual) and language.